OPTIMALISASI PEMANFAATAN PEWARNA ALAMI (NATURAL DYES) UNTUK PREPARAT MASERASI (GOSOK) TULANG - Dewi Puspita Sari; Harlita Harlita (Florea : Jurnal Biologi dan Pembelajarannya, 2020)
A method of maceration can be used for making tissue slide wich are hard as bone, teeth, and the hard other preparation. The purpose of making maceration slide is to be identify parts bone tissue main the thigh or teeth. Benefits making maceration slide is the quality and satisfaction result from preparation and easy check microtechnique preparation about the parts of the structure of havers system. The effort to make maceration slide better quality is to apply dyesstuff. In general colourful ingredients often worn is dyestuff synthetic. Dyestuff this sometimes it is difficult to get applied in scholl because prices and the use of. Based on urgency that is, the use of a natural dye expected to be the solution. Coloring matter natural will ne used for staining among others (1)extract fruit beet (Beta vulgaris L), (2) Secang wood (Caesalpinia sappan L) 3) turmeric (Curcuma domestica Val). Method used in maceration with series of stages the sample collection, fixation, dealcoholization,staining, and ends with mounting. The research was showed that natural dye of Secang wood (Caesalpinia sappan L) has the best colour cosistency to dye bone maceration slide. The optimization of the best time is 15 and 30 minutes with dye secang wood. Turmeric and fruit beet having persisten staining tend to pale and not scattered evenly distributed on havers system.